tRNA Fragments Populations Analysis in Mutants Affecting tRNAs Processing and tRNA Methylation - Molla-Herman, Anahi; Angelova, Margarita T.; Ginestet, Maud; Carré, Clément; Antoniewski, Christophe; Huynh, Jean-René (Frontiers in Genetics, 2020)
tRNA fragments (tRFs) are a class of small non-coding RNAs (sncRNAs) derived from tRNAs. tRFs are highly abundant in many cell types including stem cells and cancer cells, and are found in all domains of life. Beyond translation control, tRFs have several functions ranging from transposon silencing to cell proliferation control. However, the analysis of tRFs presents specific challenges and their biogenesis is not well understood. They are very heterogeneous and highly modified by numerous post-transcriptional modifications. Here we describe a bioinformatic pipeline (tRFs-Galaxy) to study tRFs populations and shed light onto tRNA fragments biogenesis in Drosophila melanogaster. Indeed, we used small RNAs Illumina sequencing datasets extracted from wild type and mutant ovaries affecting two different highly conserved steps of tRNA biogenesis: 5’pre-tRNA processing (RNase-P subunit Rpp30) and tRNA 2’-O-methylation (dTrm7_34 and dTrm7_32). Using our pipeline, we show how defects in tRNA biogenesis affect nuclear and mitochondrial tRFs populations and other small non-coding RNAs biogenesis, such as small nucleolar RNAs (snoRNAs). This tRF analysis workflow will advance the current understanding of tRFs biogenesis, which is crucial to better comprehend tRFs roles and their implication in human pathology.